Geochronology, petrogenesis and tectonic implications of Triassic granitoids from Beishan, NW China - Li, S.; Wang, T.; Wilde, Simon; Tong, Y.; Hong, D.; Guo, Q. (Elsevier BV, 2012)
Five Triassic granitic plutons have been identified from the Beishan orogen by zircon U–Pb dating that defines two age groups: 240–238 Ma and 225–217 Ma. They belong to the high-K calc-alkaline and shoshonitic series and have alkalic and alkali-calcic characteristics, and are weakly peraluminous–metaluminous. These granitoids are mainly highly fractionated I-type granite and A-type granite. They have high Isr values (0.7049–0.7096) and negative εNd(t) values of − 0.9 to − 2.8, with Nd model ages of 0.89–1.13 Ga, suggesting a crustal contribution. They also exhibit relatively high zircon εHf(t) values (− 1.3 to + 6.1) and two-stage Hf model ages of 1.34–0.87 Ga, suggesting a mixture of mantle and various amounts of crustal components. The mantle component probably originated from underplated magmas produced by partial melting of lithospheric mantle metasomatized by fluids or melts, possibly derived from pre-existing subducted materials. The mid-Triassic (240–238 Ma) pluton has relatively high Sr/Y (15.9–41.8) ratios and MgO (1.22–3.77%) contents, with negligibly to weakly negative Eu anomalies (δEu = 0.57–0.80), indicating adakite-like features. This was likely the result of partial melting of crustal components in response to voluminous underplated mantle-derived magmas, probably linked to lithospheric delamination and asthenospheric upwelling. The Late Triassic (217–225 Ma) granitic plutons show strong negative anomalies of Eu, Ba, Nb, Ta, Sr, P and Ti. These were likely the result of fractional crystallization and crustal contamination for the granitic magma emplaced in a post-orogenic setting.